Effect of chemical disorder on the electronic stopping of solid solution alloys. (1st September 2020) - Quashie, Edwin E.; Ullah, Rafi; Andrade, Xavier; Correa, Alfredo A.
Graphical abstract: Abstract: The electronic stopping power of nickel-based equiatomic solid solutions alloys NiCr, NiFe and NiCo for protons and alpha projectiles is investigated in detail using real-time time-dependent density functional theory over a wide range of velocities. Recently developed numerical electronic structure methods are used to probe fundamental aspects of electron-ion coupling non-perturbatively and in a fully atomistic context, capturing the effect of the atomic scale disorder. The effects of particular electronic band structures and density of states reflect in the low velocity limit behavior. We compare our results for the alloys with those of a pure nickel target to understand how alloying affects the electronic stopping. We discover that NiCo and NiFe have similar stopping behavior as Ni while NiCr has an asymptotic stopping power that is more than a factor of two larger than its counterparts for velocities below 0.1 a.u.. We show that the low-velocity limit of electronic stopping power can be manipulated by controlling the broadening of the d -band through the chemical disorder. In this regime, the Bragg's additive rule for the stopping of composite materials also fails for NiCr.